2020
DOI: 10.3762/bjnano.11.100
|View full text |Cite
|
Sign up to set email alerts
|

Scanning tunneling microscopy and spectroscopy of rubrene on clean and graphene-covered metal surfaces

Abstract: Rubrene (C42H28) was adsorbed with submonolayer coverage on Pt(111), Au(111), and graphene-covered Pt(111). Adsorption phases and vibronic properties of C42H28 consistently reflect the progressive reduction of the molecule–substrate hybridization. Separate C42H28 clusters are observed on Pt(111) as well as broad molecular resonances. On Au(111) and graphene-covered Pt(111) compact molecular islands with similar unit cells of the superstructure characterize the adsorption phase. The highest occupied molecular o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This is not too unusual, as epitaxial graphene has been often—although not always 25 reported to passivate metal–organic interfaces. 56 60 Nonetheless, the HAT monolayer appears to be commensurate with the graphene substrate. This is in contrast to weakly interacting metal–organic systems for which normally incommensurate molecular overlayer structures have been reported, 61 64 while commensurate overlayer structures are (almost) only formed when the molecule substrate interactions exceed the intermolecular interactions, that is, the molecules want to interact in clearly preferred ways with the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…This is not too unusual, as epitaxial graphene has been often—although not always 25 reported to passivate metal–organic interfaces. 56 60 Nonetheless, the HAT monolayer appears to be commensurate with the graphene substrate. This is in contrast to weakly interacting metal–organic systems for which normally incommensurate molecular overlayer structures have been reported, 61 64 while commensurate overlayer structures are (almost) only formed when the molecule substrate interactions exceed the intermolecular interactions, that is, the molecules want to interact in clearly preferred ways with the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene, perhaps the most studied 2D material, has been successfully shown to prevent decomposition of organic molecules on reactive surfaces , and inhibit charge transfer . Even if the decoupling is not fully achievedit is most effective when the graphene–substrate interactions are also weak , a graphene buffer layer does efficiently weaken the interface interactions. Similar effects have been reported for other 2D materials, such as hexagonal boron nitride, MoS 2 , and others. Such buffer layers can also modify the molecular orientation compared to the molecular orientation without a buffer layer. This change in orientation can be limited to the first adsorbed layer but also extended to further layers, ,, which in turn further influences the electronic properties of the molecular film. , …”
Section: Introductionmentioning
confidence: 81%
“…It has been shown that a buffer layer interposed between the substrate and the molecular film can improve the crystallinity of the latter and reduce the electronic coupling with the support [22]. The buffer layer can either be a thin oxide film [23][24][25][26] or a single layer of 2D material, such as graphene [27,28], hexago-nal boron nitride [29][30][31] and MoS 2 [32,33]. Moreover, an organic layer inserted between the substrate and the overlayer has been shown to be effective in improving the order of the molecular film [34,35] or restoring its original electronic structure [36][37][38].…”
Section: Introductionmentioning
confidence: 99%